1999
DOI: 10.1021/bi991179x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C-Terminal Helix 9 in the Stability and Ligandin Function of Class α Glutathione Transferase A1-1

Abstract: Helix 9 at the C-terminus of class alpha glutathione transferase (GST) polypeptides is a unique structural feature in the GST superfamily. It plays an important structural role in the catalytic cycle. Its contribution toward protein stability/folding as well as the binding of nonsubstrate ligands was investigated by protein engineering, conformational stability, enzyme activity, and ligand-binding methods. The helix9 sequence displays an unfavorable propensity toward helix formation, but tertiary interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 41 publications
(113 reference statements)
3
70
0
1
Order By: Relevance
“…Although the exact location of the ANS binding site in the hGSTA1 subunit is unknown, a fluorescence resonance energy-transfer study indicated binding of ANS at the V-shaped cleft along the dimer interface [11]. The C-terminus of helix 9, also located near the dimer interface, is adjacent to the ANS site and modulates ANS binding [28]. Other non-substrate ligands that bind the V-shaped cleft include aflatoxin B " [12], oestradiol disulphate [13] and 5-o[2-[(acetyl)amino]ethyl]aminoq-naphthalene-1-sulphonic acid (AEDANS) [42].…”
Section: Discussion Ans Binding Site and Stoichiometrymentioning
confidence: 99%
See 3 more Smart Citations
“…Although the exact location of the ANS binding site in the hGSTA1 subunit is unknown, a fluorescence resonance energy-transfer study indicated binding of ANS at the V-shaped cleft along the dimer interface [11]. The C-terminus of helix 9, also located near the dimer interface, is adjacent to the ANS site and modulates ANS binding [28]. Other non-substrate ligands that bind the V-shaped cleft include aflatoxin B " [12], oestradiol disulphate [13] and 5-o[2-[(acetyl)amino]ethyl]aminoq-naphthalene-1-sulphonic acid (AEDANS) [42].…”
Section: Discussion Ans Binding Site and Stoichiometrymentioning
confidence: 99%
“…that is implicated in ligandin function [28]. The role of the ultimate residue Phe-222, located near the cleft at the dimer interface, in ligandin function was also addressed.…”
Section: Figure 1 the Structure Of Ansmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the CD-Search in NCBI's CDD, the predicted protein sequence of MgGSTa cDNA was matched to the GST_N_alpha_like and GST_C_alpha_like, containing an H-site which is a substrate binding site in the C-terminal [14]. The longer alpha C-terminal also forms an a-helix, which is thought to be important to dimer stabilization and affects both the GSH-binding rate and the ionization state of the catalytically essential residue Tyr [15,16]. The sigma class GSTs are lacking in both components of the ball-and-socket interface, and rely on a Tyr residue for GSH stabilization in the G-site [12], which was also found in the sequence of MgGSTS1, MgGSTS2 and MgGSTS3.…”
Section: Discussionmentioning
confidence: 99%